KELAYAKAN LORA UNTUK JARINGAN KOMUNIKASI SISTEM PENGELOLAAN AIR DI POLITEKNIK NEGERI SAMARINDA - Prihadi Murdiyat; Abdul Hamid Kurniawan; Sunu Pradana (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2021)
Abstract—A water management system is being developed in Politeknik Negeri Samarinda (Polnes). The system consists of a number of sensor node (SN) that is always connected to a gateway/sink. Communication network between SNs and gateway is considered to utilize radio technology. As the campus area reaches 10 hectare, long range (LoRa) radio technology might be the candidate. Eventhough LoRa, in its specification, could cover the distance of around 15 km in line of sight condition, Polnes campus that has hilly terrain with several storey buildings may reduce the coverage of LoRa. Hence, in this research, the received signal strength (RSSI) was measured to find the possibility of LoRa being the communication network infrastructure. At the location where the gateway would be installed, a 433 Mhz LoRa transmitter was operated to continuously send data packets. A LoRa receiver was brought to every future SN locations to measure the RSSI. The measurement by the receiver that was equipped with a rubber duck antenna (3 dBi gain) showed that the RSSI is between -107 dB to -85 dB for the distance of up to 165 meter. Meanwhile, by the use of a Yagi antenna with the gain of 7.37 dBi, the RSSI value is between -100 dB to -80 dB. All of those results verify that LoRa is capable for the communication infrastructure of Polnes water management system.